Remote Working in the COVID-19 Pandemic: Results From a Questionnaire on the Perceived Noise Annoyance - Puglisi, Giuseppina Emma; Di Blasio, Sonja; Shtrepi, Louena; Astolfi, Arianna (Frontiers in Built Environment, 2021)
Noisiness in the working environment was largely proved to have effects on the working activity and performance. To limit the spreading of the COVID-19 pandemic in the first wave between March and May 2020, Italian workers have massively started performing remote working. Insights on the subjective perception of noise annoyance under the remote working settings were thus necessary. Workers from a university and from several large and small Italian companies, resulting in 1934 participants overall, answered to a questionnaire on the perception of noise annoyance in the remote working environment. A total of 57% of the responding workers stated to be sensitive to noise. The questionnaire was delivered online; data were recorded anonymously and then aggregated for statistical analyses. Results show that 55% of the workers perform their activity in an isolated room of the home environment, 43% in a shared room (e.g., kitchen, living room) and 2% in an outdoor space, with the majority of workers (57%) performing activity without other people in the environment. Among the noise sources investigated, 25% of workers recognize the noise generated by people (e.g., talking, moving, calling, listening to music) as the main source of disturbance. The negative consequences of noise annoyance during the remote working hours are mainly related to a loss of concentration and to a difficulty in relaxing. Furthermore, workers reported to get easily irritated by noise generated from the neighborhoods or from the house mates as it tends to distract from finishing a task.